Perceptions and self-efficacy in online learning: Do students' characteristics and access to technology matter? - Fearnley, Marissa; Fabia, Jose Noel; Caballes, Dennis (South Sulawesi Education Development, 2025)
While online learning has become the delivery mode of choice to facilitate flexible or distance learning amid the COVID-19 pandemic, this alternative approach to instruction has challenged the entire educational system in the Philippines. Survey data from 2027 students from a private college were analyzed using nonparametric statistical tests to examine how perceptions and self-efficacy in online learning are affected by students’ characteristics and access to technology. Findings suggest that, in general, college students have moderate to high perceptions and self-efficacy when it comes to online learning. When students’ characteristics were compared, gender, academic track, and prior online learning experience showed significant differences in the two scales. Year level and the number of units enrolled in by students did not have any significant effect. Factors related to technology access, namely, device ownership, device sharing, Internet connectivity, and type of subscription, were also investigated. Both Internet connectivity and the type of subscription were significant factors that impact how learners view online learning and how competent they are in accomplishing online tasks. When online learning perceptions and online learning self-efficacy were correlated, highly significant positive associations among the subscales were obtained.